2021
DOI: 10.1039/d0cp05752e
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical prediction by DFT and experimental observation of heterocation-doping effects on hydrogen adsorption and migration over the CeO2(111) surface

Abstract: The addition of dopants with a small ionic radius led to strong binding of H atoms, and the balance of H+ reactivity (mobility) and H+ coverage was fundamentally important for high H+ conductivity and catalysis involving surface protonics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 59 publications
(59 reference statements)
1
15
0
Order By: Relevance
“…Results of the present study demonstrated that the surface structure relaxation during adsorption dominates the adsorption behaviour in the adsorption without applying the electric field of CO 2 molecules as well as a recent study about H atom adsorption [20].…”
Section: Co 2 Adsorption With the Electric Fieldsupporting
confidence: 82%
See 1 more Smart Citation
“…Results of the present study demonstrated that the surface structure relaxation during adsorption dominates the adsorption behaviour in the adsorption without applying the electric field of CO 2 molecules as well as a recent study about H atom adsorption [20].…”
Section: Co 2 Adsorption With the Electric Fieldsupporting
confidence: 82%
“…On the other hand, CeO 2 has f electrons and is known as a semi-conductor, so CeO 2 adsorption can be greatly controlled by applying an electric field, and its performance can be easily tuned by hetero-cation doping; since the valence of Ce can be changed, there is a high level of structural freedom through doping with cations of different valence states. Therefore, DFT calculations were performed using CeO 2 doped with various hetero-cations, 20 which have been studied as CO 2 adsorbents 21,22 and as supports for CO 2 -activation catalysts. 23,24 Then, differences between the doped cations were investigated with regard to the changes in the CO 2 adsorption performance by application of the electric field.…”
Section: Introductionmentioning
confidence: 99%
“…Reportedly, H atoms tend to join electron-deficient surface oxygen sites because the electron of the H atom can transfer easily to oxygen sites (known as Lewis acid sites). 47,50–52 Therefore, we concluded that the formation of the electron-rich surface oxygens by the subtle Ba 2+ substitution provoked the decrease in the H atom adsorption energy. Furthermore, the obtained DOS shapes (depicted in Fig.…”
Section: Resultsmentioning
confidence: 82%
“…Previous results verified that activated H atoms over the oxide surface can facilitate N 2 cleavage via unstable species (N 2 H intermediate in the case of NH 3 synthesis) in the electric field. 47 In this mechanism, the formation rate of N 2 H intermediate determines the overall reaction rate. Therefore, the ability of donating H atoms to N 2 is an important factor for NH 3 synthesis in the electric field.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation